Nickel-Catalyzed Regioselective Access to Dibenzo[c,f][1,2]thiazepine 5,5-Dioxides and Dibenzo[b,e]azepines - Mandal, Uma Sankar; Ahamed, Sk. Shamim; Ghosh, Tapas (Synthesis, 2025)
An effective technique that yields dibenzo[c,f][1,2]thiazepine 5,5-dioxide and dibenzo[b,e]azepine derivatives through nickel-catalyzed regioselective intramolecular acetylene hydroarylation is reported. The developed method proceeds without the need for any additional external ligand. This protocol tolerates different functional groups and furnishes the desired products regioselectively in good to excellent yields.
Keywords: nickel catalysis; azepines; sultams; regioselectivity; acetylene hydroarylation